The Effect of Green Marketing on Repurchase Intention of Rapoviaka Simple Products with Green Consumerism as a Moderating Variable - Sulistiawati; Sutomo, Maskuri; Muzakir; Farid (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of eco-friendly marketing on repurchase intention for Rapoviaka Simple products, with eco-friendly consumption as a moderating variable. Using a quantitative, associative-causal approach, data were collected from 96 respondents through purposive sampling and analyzed with SmartPLS 4. The findings reveal that eco-friendly marketing significantly and positively influences repurchase intention, while eco-friendly consumption strengthens this relationship. The study supports the Theory of Planned Behavior in explaining repurchase intention toward eco-friendly products and offers practical insights for developing effective green marketing strategies. Keywords: Green Marketing, Repurchase Intention, Green Consumerism